HRM Practices in Insurance Companies: A Case Study of Bangladesh - Mohammad Nazim Uddin (Journal of Accounting, Business and Management (JABM), 2014)
The importance of HR has been well recognized in business organization for the productivity and quality management of the concerned. The main purpose of the study is to examine the existing HRM practices in insurance sector of Bangladesh. The study has used the structural questionnaire for primary data that includes various dimensions on HRM. The study has also used secondary data relevant to articles, journals, books, and conference papers for theoretical development. In order to validate the findings, the necessary statistical measures include 5 point Likert scale, mean, and rank are used in the study. The study revealed that the present HRM in insurance sector has made some substantial problems that hinder the job satisfaction and productivity of insurance organization in Bangladesh. These results of the study could be useful for national entrepreneur of insurance business, regulator body of insurance organization, and policy makers that seek to improve the productivity and quality as they suggest the need for implementation of simulative policies for the development of insurance industry.